The prevalence of polycystic ovary syndrome in adolescents: A systematic review and meta-analysis - Marzieh Saei Ghare Naz; Fahimeh Ramezani Tehrani; Hamid Alavi Majd; Fazlollah Ahmadi; Giti Ozgoli; Farzaneh Rashidi Fakari; Vida Ghasemi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Polycystic ovarian syndrome is an endocrine disorder with many complications. This syndrome is a growing concern among adolescents around the world, with varying reports of its prevalence in different parts of the world. Objective This study aimed to determine the prevalence of polycystic ovary syndrome in adolescents by a systematic review and meta-analysis. Materials and Methods In this study, a search for published articles with an English language limitation and without a time limit was done in different databases (Scopus, PubMed, and Web of Science, Emabse and Cochrane) in January 2019. The 12 studies that met the criteria for entering a qualitative assessment scale of 5 and higher were subjected to systematic review and meta-analysis. Egger and Begg's tests were used to check the publication bias. Data were analyzed with STATA software, version 11.1. Results Twelve studies were included for meta-analysis. The total number of participants in the study was 149,477. The average quality score of all studies was 8.67 (range: 5-10). The prevalence of polycystic ovarian syndrome in adolescents based on the Rotterdam criteria was 11.04% (95% CI: 6.84-16.09%), based on the National Institute of Health criteria, it was 3.39% (95% CI: 0.28-9.54%), and based on Androgen Excess and Polycystic Ovary Syndrome Society, it was 8.03% (95% CI: 6.24-10.01%) Conclusion The result of this study showed that there is a variation in the prevalence of PCOS in adolescents based on different criteria; we suggest more community-based studies among adolescences in different parts of the world.